Association of perioperative use of statins, metformin, and aspirin with recurrence after curative liver resection in patients with hepatocellular carcinoma: a propensity score matching analysis - Khajeh, Elias; Aminizadeh, Ehsan; Dooghaie Moghadam, Arash; Ramouz, Ali; Klotz, Rosa; Golriz, Mohammad; Merle, Uta; Springfeld, Christoph; Chang, De-Hua; Longerich, Thomas; Büchler, Markus W.; Mehrabi, Arianeb (Cancer medicine, 2023)
Background Statins, metformin, and aspirin have been reported to reduce the incidence of hepatocellular carcinoma (HCC). However, the effect of their perioperative use on survival outcomes of HCC patients following curative liver resection still remains unclear. Method Three hundred and fifty three patients with a first diagnosis of HCC who underwent curative liver resection were included. Propensity score matching analysis with a users: nonusers ratio of 1:2 were performed for each of the medications (statins, metformin, and aspirin). Overall survival (OS) and recurrence-free survival (RFS) were evaluated and multivariable Cox proportional hazard analysis was performed. Results Sixty two patients received statins, 48 patients used metformin, and 53 patients received aspirin for ≥90 days before surgery. None of the medications improved OS. RFS of statin users was significantly longer than that of nonusers (p = 0.021) in the matched cohort. Users of hydrophilic statins, but not lipophilic ones had a significantly longer RFS than nonusers. Multivariable analysis showed that statin use significantly improved RFS (hazard ratio [HR]: 0.41, 95% confidence interval [CI]: 0.17-0.97, p = 0.044). No difference was seen in RFS between metformin users and nonusers. Among patients with diabetes, RFS was nonsignificantly longer in metformin users than in non-metformin users (84.1% vs. 60.85%, p = 0.069) in the matched cohort. No difference in postoperative RFS was seen between aspirin users and nonusers. Conclusion Preoperative use of statins in patients with HCC can increase RFS after curative liver resection, but metformin and aspirin were not associated with improved survival. Randomized controlled trials are needed to confirm the findings of the present study.